Explorations in topology : map coloring, surfaces, and knots - Gay, David (Burlington, Mass. : Elsevier, 2007)
"David Gay provides his readers with a rich experience with low-dimensional topology, enhances their geometrical and topological intuition, empowers them with new approaches to solving problems, and provides them with experiences that would help them make sense of a future, more formal topology course. The innovative story-line style helps readers connect with the material and "learn by doing"." "Explorations in Topology is ideal for use in an introductory course for junior or senior mathematics majors and high school mathematics teachers; it is also a great resource for mathematicians/mathematics educators interested in curriculum development and original approaches to the teaching of advanced undergraduate mathematics."--BOOK JACKET.
Keywords: Topology